Status of Prenatal Assistance services for Syphilis Infected Pregnant Women on Region of Baixada Santista, Sp, Brazil - Roberto Focaccia; Patricia Gomes Di Napoli; Karla Fabiana Begosso Sampaio da Fonseca Carbonari; Aline Andruskevicius de Castro; Agatha Rossi Dias; Amanda Machado Amaral de Freitas; Ana Carolina C Cossich; Allyne Fernandes Couto; Beatriz Bandini Gonçalves; Bruna Oliveira Ambrogi; Camila Salles Lopes; Carolina Zavatini Pereira; et al. (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Objective: To analyze the status used in prenatal assistance on pregnant women infected with syphilis, of São Vicente, general region of Santos, SP, Brazil.  Methods: This was a descriptive cross-sectional study, retrospective study in the medical records of 162 patientes, between 2014 and 2016, in basic health units.  Results: Close to 35% of the patients' partners did not receive treatment. Only 30% of the pregnant women attended the recommended consultations, and only 15% followed the monthly serological follow-up. Most of the medical records were incomplete. Conclusions: The prenatal care in the study area reveals failures indicating the need greater medical staff training.